Clima organizacional y su influencia en el ambiente laboral de los funcionarios de la Cooperativa de Ahorro y Crédito San Antonio de la ciudad de Babahoyo - Córdova Caicedo, Alva Yuliza (2021)
The organizational climate is an important element for the development of organizations, because it has a direct impact on the development of their employees, and therefore on the correct execution of their processes and activities. This case study does an analysis of the organizational climate and how it influences the working environment of the officials of the San Antonio savings and credit union, taking as a specific analysis unit the business area of the Babahoyo branch, given the influx of customers that it has on a daily basis, and the type of work that is done. The study of the working environment as an independent variable establishes the importance of properly managing the organizational climate in institutions. For the development of research, the inductive and deductive-synthetic method is used, initiating with a documentary analysis of the main theories about organizational climate variables and working environment, based on bibliography by authors who are experts in the subject. Subsequent field research is carried out on the entity, through a survey of officials. The results showed the poor working climate of the officials surveyed, and determined potential causes related to the organizational climate, which eventually led to the direct impact of the organizational climate on the work environment, and the need to generate actions aimed at improving it to increase the level of employee satisfaction.